Transformerless dc Converter for Distributed Solar Power Generation System - Heri Suryoatmojo; Akbar Faiz; Mochamad Ashari; Ronny Mardiyanto (Department of Electrical Engineering ITS and FORTEI, 2017)
There are two types of distributed solar power generation system stand-alone system and grid-connected system. In grid-connected system usually are equiped with additional transformer to transfer the energy from solar power to the grid. However, it has resulted in considerable cost in providing these systems. Therefore in this reserach develops boost transformerless inverter system. The proposed system consists of a boost converter and transformerless inverter. Boost converter is used to increse the dc voltage yield by photovoltaic (PV) and delivered to the grid by mean of transformerless inverter.In order to maximize the power from PV, the proposed system is also designed with Maximum Power Point Tracking (MPPT) by changing the value of modulation index in the transformerless inverters. From the simulation results show that the system can work effectively in a variety conditions such as light intensity changed and fluctuating in the grid voltage side. Keywords: Inverter Transformerless, Boost Converter, MPPT, Photovoltaic.